Can macroalgae contribute to blue carbon? An Australian perspective. (25th June 2015) - Hill, Ross; Bellgrove, Alecia; Macreadie, Peter I.; Petrou, Katherina; Beardall, John; Steven, Andy; Ralph, Peter J.
Abstract: Macroalgal communities in Australia and around the world store vast quantities of carbon in their living biomass, but their prevalence of growing on hard substrata means that they have limited capacity to act as long‐term carbon sinks. Unlike other coastal blue carbon habitats such as seagrasses, saltmarshes and mangroves, they do not develop their own organic‐rich sediments, but may instead act as a rich carbon source and make significant contributions in the form of detritus to sedimentary habitats by acting as a "carbon donor" to "receiver sites" where organic material accumulates. The potential for storage of this donated carbon however, is dependent on the decay rate during transport and the burial efficiency at receiver sites. To better understand the potential contribution of macroalgal communities to coastal blue carbon budgets, a comprehensive literature search was conducted using key words, including carbon sequestration, macroalgal distribution, abundance and productivity to provide an estimation of the total amount of carbon stored in temperate Australian macroalgae. Our most conservative calculations estimate 109.9 Tg C is stored in living macroalgal biomass of temperate Australia, using a coastal area covering 249, 697 km 2 . Estimates derived for tropical and subtropical regions contributed an additional 23.2 Tg C. By extending the search to include global studies we provide a broader context and rationale for the study, contributing to the global aspects of the review. In addition, we discuss the potential role of calcium carbonate‐containing macroalgae, consider the dynamic nature of macroalgal populations in the context of climate change, and identify the knowledge gaps that once addressed will enable robust quantification of macroalgae in marine biogeochemical cycling of carbon. We conclude that macroalgal communities have the potential to make ecologically meaningful contributions toward global blue carbon sequestration, as donors, but given that the fate of detached macroalgal biomass remains unclear, further research is needed to quantify this contribution.